Analysis of Special Order Product Pricing Using a Relevant Cost Approach: A Case Study at Puna Jaya Tempe Factory, Poso Regency - Riski Kurniawati; Abdul Kahar; Sugianto Sugianto; Jurana Jurana (International Forum of Researchers and Lecturers, 2025)
This study aims to examine, analyze, and describe the determination of selling prices for special orders using the relevant cost approach and the cost-plus pricing method at